Current status and trends of research on microplastic fugacity characteristics and pollution levels in mangrove wetlands - Chen, Bin (Frontiers in Environmental Science, 2022)
Microplastics have been widely detected in environment, such as rivers, oceans and mangrove wetlands. Mangrove wetlands are considered to be barriers to land-based plastic transport to the ocean, which requires special attention for research. Two kinds of literature reviews methods are used in this study to analysis the current research status and future trends. Characteristics of microplastics, including color, shape, size, polymer chemistry and surface microstructure are the basic information for microplastic research in mangrove wetlands. Microplastics size is the key to study the distribution and convergence, but without international standard. Characteristic of shape is vital to study its sources and environmental processes. Microplastic color affects biological predation and is an important information for studying ecological risk. The chemical composition of plastics is the key to study the fingerprint information and source and sink of microplastics. Microplastic surface microstructure is an important basis for studying adsorption behavior and aging process. Mangrove microplastic studies in China are mainly in southern and southeastern coasts, and microplastic pollution is somewhat more serious in Fujian, Guangdong and Guangxi than in Hainan. While foreign studies on mangrove microplastics are mainly concentrated in Southeast Asia, the Middle East and South America. Overall, microplastic contamination was detected in the major distribution areas of mangroves worldwide and was correlated with mangrove density and human activities. Future study should focus on microplastic transport process, ecological risks assessments, the effects to carbon cycle, and policies and management plans for microplastic pollution.